The book eaters - Dean, Sunyi (TOR/Tom Doherty Associates, 2022)
"Sunyi Dean's The Book Eaters is a contemporary fantasy debut. It's a story of motherhood, sacrifice, and hope; of queer identity and learning to accept who you are; of gilded lies and the danger of believing the narratives others create for you. Out on the Yorkshire Moors lives a secret line of people for whom books are food, and who retain all of a book's content after eating it. To them, spy novels are a peppery snack; romance novels are sweet and delicious. Eating a map can help them remember destinations, and children, when they misbehave, are forced to eat dry, musty pages from dictionaries. Devon is part of The Family, an old and reclusive clan of book eaters. Her brothers grow up feasting on stories of valor and adventure, and Devon-like all other book eater women-is raised on a carefully curated diet of fairytales and cautionary stories. But real life doesn't always come with happy endings, as Devon learns when her son is born with a rare and darker kind of hunger-not for books, but for human minds"--